Nilai Filosofis Peralatan Tradisional Terhadap Karakter Perempuan Jawa dalam Pandangan Masyarakat Pesisir Utara Jawa Tengah - Suryadi, M (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The uniqueness of Javanese society, especially the Javanese people north coast of Central Java is a way of looking at the values of life. One of the values of the life of the Javanese people is attached to traditional household appliances. Traditional tools have lexical meanings, cultural meanings, and philosophical values. These three components are captured in the name of the equipment. Traditional tools of coastal Javanese society gradually began to be abandoned by their owners and began to be replaced with modern equipment. As a result, inherent philosophical values begin to be forgotten. Research location in Demak Regency. Data collection methods used were observation, in-depth interviews, and focus group discussions.The data analysis method used is a description of the lexical component: the description of the lexical meaning and cultural meaning.Description of internal culture: elaboration of philosophical values.Research findings: each traditional equipment name has a correlation between the lexical meaning of cultural meaning, and cultural meaning of its philosophical value.The traditional equipment function of the coastal Javanese community is attached to referents. Philosophical values are attached to references.